2013
DOI: 10.1021/jp4020367
|View full text |Cite
|
Sign up to set email alerts
|

Role of Magnetism in Catalysis: RuO2 (110) Surface

Abstract: Angular momentum seems to not be conserved in chemical reactions where one of the reactants is magnetic; consequently, such reactions show a high activation barrier. An example is the production of hydrogen by electrolysis of water: practically all losses occur in the production of (magnetic) oxygen. Anodes with a low overvoltage (a measure of the losses) are based on the ruthenium dioxide (110) surface. First-principles electronic structure calculations show that this surface itself carries magnetic moments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(130 citation statements)
references
References 40 publications
7
123
0
Order By: Relevance
“…45,46 Therefore, this type of hydrous silica sheets deserves further experimental and theoretical investigations. For example, one may deposit the hydrous silica sheets onto nanocrystals (NCs) to reach the ultimate goal of atomic coating by means of suitable sol-gel approaches.…”
Section: Further Discussion and Outlookmentioning
confidence: 99%
“…45,46 Therefore, this type of hydrous silica sheets deserves further experimental and theoretical investigations. For example, one may deposit the hydrous silica sheets onto nanocrystals (NCs) to reach the ultimate goal of atomic coating by means of suitable sol-gel approaches.…”
Section: Further Discussion and Outlookmentioning
confidence: 99%
“…Nevertheless, the detailed mechanism underlying the O−O bond formation remains unresolved . Although spin is rarely discussed in works exploring artificial photosynthesis, recent theoretical studies suggest that the overpotential required to split water is linked to restrictions on the electrons’ spin in generating a ground state triplet oxygen molecule ,. In a recent experimental work, it has been shown that when the anode in the water‐splitting cell is coated with chiral molecules, the overpotential is reduced …”
Section: The Ciss Effectmentioning
confidence: 99%
“…Ruthenium oxide (RuO 2 ) presents several attractive properties such as low resistivity, 1 high thermal stability, 2 good diffusion barrier capability, 3 excellent catalytic performance, 4,5 and easy patterning. 6 These interesting properties can make RuO 2 a suitable candidate for a large number of applications.…”
Section: Introductionmentioning
confidence: 99%